Saturday

August 23, 2014

August 23, 2014

Posted by **al** on Wednesday, January 12, 2011 at 11:34pm.

5x - y=-1

15x=2y

- math -
**Haley**, Wednesday, January 12, 2011 at 11:42pmsolve the first equation for y.

5x-y=-1 subtract 5x from both sides

-y=-1-5x divide by -1

y=1+5x

now, plug this answer in for y in the second equation.

15x=2y

15x=2(1+5x)

15x=2+10x

5x=2

x=.4

plug this(x=.4) into the equation for y.

y=1+5x

y=1+5(.4)

y=1+2

y=2

therefore, x=.4 and y=2 or (.4, 2)

- math -
**al**, Thursday, January 13, 2011 at 12:37amactually that does not work out, plug x and y into original equation...

- math -
**al**, Thursday, January 13, 2011 at 12:39amactually that does not work out, plug x and y into original equation...

y=1+2

y=3

then it works out

**Related Questions**

Math - Solve by Substitution method. 15x-20y=-7 15y=4+5x

math - Solve by elimination 5x+y=2 3x+y=1 This is what I got : 3(5x+y=2) -5(3x+y...

Algebra help! - 1.) Solve the system by triangularizing the augmented matrix and...

Geometry :( - this maths problem is wrecking my head.... 1.find the points of ...

algebra - i need help with these problems (either a solution or how to plug them...

math - solve each system of equations by substitution. y=3x-9 please help ...

Substitution Method-Plz help - Use the Substitution method to solve the system ...

substitution method - 1. y=x+4 y+3x 2. y=3x-10 y= 2x-5 3.x=-2y+! x=y-5 4.y=5x+5 ...

Math - f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(...

Math - f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(...